The Artificial Empire. The Indian Landscapes of William Hodges. By Valdas Jaskūnas - Tillotson, Giles (Acta Orientalia Vilnensia, 2005)
Center of Oriental Studies, Vilnius University GILES TILLOTSON. The Artificial Empire. The Indian Landscapes of William Hodges, Richmond: Curzon Press, 2000, 162 pp., 60 black and white & 8 colour illustrations. ISBN 0-7007-1282-8, £70